Experience, Knowledge, and Risk Perception Among Adventure Tourism Workers in Yogyakarta - Ahmad Afif Mauludi; Rini Puspita Dewi; Muhammad Azrin Karim; Tri Arini; Dwina Anggraini; Tia Nurhidayanti; Arif Sulfiantono (Journal of Research on Business and Tourism, 2026)
This study examined occupational health and safety (OHS) risk perception and its influencing factors among adventure tourism workers in Yogyakarta, Indonesia. A cross-sectional, quantitative design was used with data collected via self-administered online questionnaire from 114 workers aged 17 to 58 years. Non-parametric tests were applied: Spearman's Rho, Kendall's Tau, Mann-Whitney U, and Kruskal-Wallis H. Workers rated most hazards at the "Medium Risk" level, though organizational failures and external conditions received consistent "High Risk" ratings. Contrary to expectations, education, work experience, and OHS knowledge all showed negative correlations with risk perception, indicating that familiarity with the job may foster complacency rather than heightened vigilance. Work-related stress and prior injury history, by contrast, correlated positively with risk perception. These findings suggest that experienced workers may develop overconfidence that dulls their sensitivity to occupational hazard. Knowledge-based training alone does not appear sufficient to counter this tendency. The study argues for OHS programs that target risk perception recalibration through experiential methods, and urges management to treat equipment quality and organizational preparedness as priority concerns.